2007
DOI: 10.3928/01913913-20070701-04
|View full text |Cite
|
Sign up to set email alerts
|

Causes of Visual Impairment in Children: A Study of 3,210 Cases

Abstract: <h4>PURPOSE</h4> <p>To determine causes of visual impairment in children at the Low Vision Service of the Ophthalmic Clinic at the University of São Paulo and at the Brazilian Association for the Visually Impaired People (Laramara), located in São Paulo, Brazil.</p> <h4>PATIENTS AND METHODS</h4> <p>This study evaluated 3,210 visually impaired children (49% female, 51% male; average age, 5.9 years). Visual impairment was present in 57% (visually impaired group) and 43%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(11 citation statements)
references
References 10 publications
1
9
0
1
Order By: Relevance
“…Despite several population studies that examined the prevalence of IRDs (4)(5)(6), there are only a few that reported the incidence of IRDs or IRD-related blindness on a population scale (7)(8)(9)(10)(11). A significant proportion of childhood blindness, across different countries, has been attributed to IRD (9,10,(12)(13)(14)(15). This is consistent with data from the UK in which 13% of all childhood blindness certificates were attributed to IRD (16).…”
Section: Introductionsupporting
confidence: 58%
“…Despite several population studies that examined the prevalence of IRDs (4)(5)(6), there are only a few that reported the incidence of IRDs or IRD-related blindness on a population scale (7)(8)(9)(10)(11). A significant proportion of childhood blindness, across different countries, has been attributed to IRD (9,10,(12)(13)(14)(15). This is consistent with data from the UK in which 13% of all childhood blindness certificates were attributed to IRD (16).…”
Section: Introductionsupporting
confidence: 58%
“…The findings of this study compare well with other studies conducted in India, Tehran, Brazil, Thailand, Germany and in the Netherlands which identified retinal disorders as the most common cause of blindness. 13,[15][16][17][18] Anterior segment disorders were a more common cause of vision loss in studies performed in Uganda and Ethiopia which might reflect a high prevalence of infectious diseases and vitamin A deficiencies in these states. 19,20 As our study was conducted among the students in the school of blind, the two common diseases which are the important cause of low vision (cataract and refractive error) was not seen as a major cause of vision loss in our study population.…”
Section: Discussionmentioning
confidence: 99%
“…Congenital glaucoma is a major cause of childhood blindness worldwide, with variable birth prevalence in different populations worldwide, 1 and is responsible for 10.8% of all visual impairments in children. 2 The disease is usually managed surgically, with medical treatment playing a temporary or an adjunctive role. Multiple surgical modalities have been described, however surgery in a buphthalmic eye with disturbed anatomy is challenging and is associated with higher failure rates and multiple complications than in adults.…”
Section: Introductionmentioning
confidence: 99%
“…Congenital glaucoma is a major cause of childhood blindness worldwide, with variable birth prevalence in different populations worldwide, 1 and is responsible for 10.8% of all visual impairments in children. 2 …”
Section: Introductionmentioning
confidence: 99%